Critical Stylistics od " History of ministers" - Zahra Jafariyan; Narges Oskouie (مطالعات زبانی و بلاغی)
The prominent trait of Seljuk's monarchy, especially the early kings of this dynasty, is Iranian-Islamic bureaucracy, and effective presence of Iranian scientist ministers, who were political theorists themselves. this incident caused writing the separated histories about this important position, and its result is production of some works about ministers, and bureaucrats action, and character in this era; " history of minister" written by Abu Raja Qomi is one of these important historical works. Studying the styles levels of the book of "history of ministers" for representation, and analyzing of hidden ideology in language, and literature of this text is the main of this paper by using the research method. Findings of this paper include the following data: 1- at ideological level, author expressly, and partially narrates his personal judgments besides restating the history about bureaucrats' job skills, and moralities by using Islamic, and moral teachings. 2- At linguistic level, the privilege is by state nominal indicators, religious, and moral labeled words, and also mental words of religion, and moral fields that imply on religious prejudice, and tendencies of author. 3- At grammatical level, by using the simple, and separated sentences, active grammatical voices, declarative decisive form, author protect expressly uses of declarative phrases. 4- At rhetoric level, abundant use of eloquence means is lesser at service of ideology, and are for beauty of expression more. 5- at expertise level, with an expressive- Persuasive approach to prove, and encourage of its value system.